Patologi Birokrasi dalam Sinkronisasi Data Stunting di Kabupaten Jombang - Winanda, Nieke Rudyanty; Destyananda, Nanditya Putri; Utomo, Priyono (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
Stunting is a condition of failure to thrive in children and toddlers caused by acute malnutrition. Data shows that the prevalence of stunting in Indonesia is relatively high. Likewise, in Jombang Regency. One of the problems that is quite influential in accelerating the reduction of stunting, especially in Jombang Regency, is data synchronization. Synchronizing this data is one of the obstacles to reducing stunting. Various problems occur in data synchronization, one of which is bureaucratic pathology. This research uses Max Weber's theory of ideal bureaucracy as well as theories about bureaucratic pathology. The method used in this research is qualitative with primary and secondary data sources. The data collection methods used were interviews, observation, and documentation, with data analysis methods using the Miles and Huberman model. The results of this study indicate a bureaucratic pathology in the synchronization of stunting data in Jombang Regency. The most fundamental is the lack of uniformity in the use of stunting data collection applications, resulting in data held by each Regional Apparatus Organization (APO). This unsynchronized stunting data is one of the obstacles to accelerating stunting reduction in Jombang Regency. This, of course, constitutes a bureaucratic pathology in the synchronization of stunting data. If this bureaucratic pathology can be minimized, it will reduce obstacles to synchronizing stunting data in Jombang Regency.